Predisposing Risk Factors Associated with Acute Myocardial Infarction (AMI): A Review - Mishra Mritunjay; DVSS Ramavataram (Indian Journal of Forensic Medicine & Toxicology, 2021)
Among non-communicable diseases, cardiovascular diseases are major contributors to the resulting morbidityand mortality all over the world and India is no exception. Being one of the densely populated country andcategorized as developing country, the proportion of subjects who are being afflicted with this disease hasbeen progressively increasing. One of the leading causes for cardiovascular complications is myocardialinfarction. The incidence of Acute Myocardial infarction has been observed across all the populations andfrom early adulthood to old age. Over the years there has been change in life style and dietary habits whichis further contributing to increased prevalence. A number of risk factors have been found to be causativefactors for development of the disease. Which include, genetic, environmental, life style modifications etc.The risk factors can be categorized in modifiable and non-modifiable risk factors. Those factors which canbe controlled are categorized as modifiable and by changing them the risk level can be decreased whereasnon modifiable risk factors cannot be changed and by knowing them one can assess the amount of riskinvolved. The present review is focused on various risk factors which are known to cause cardiovasculardiseases and the role of each risk factor in the development of Acute Myocardial Infarction.